PRODUCTION OF WIRE RML OF SQUARE PROFILE IN CONDITIONS OF BELORUSSIAN METALLURGICAL WORKS - D. G. Sachava; O. I. Ignatenko; E. V. Shamanovskaja (Литьë и металлургия)
It is shown that at using of profile (square) wire RML in conditions of RUP «BMZ» for production of pipes of high pressure their production is cheapened, what attracts interest of consumer.